Addition of low-dose ketamine to midazolam and low-dose bupivacaine improves hemodynamics and postoperative analgesia during spinal anesthesia for cesarean section - Ahmed Sobhy Basuni (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Spinal anesthesia for cesarean section (CS) is associated with an incidence of hypotension of 60-94%. This study hypothesizes that intrathecal combination of low-dose ketamine, midazolam, and low-dose bupivacaine improves hemodynamics and postoperative analgesia compared with fentanyl and low-dose bupivacaine during CS. Material and Methods: Fifty parturients undergoing elective CS were randomized equally to receive ketamine (10 mg), midazolam (2 mg) and 0.5% hyperbaric bupivacaine (8 mg) in group ketamine-midazolam-bupivacaine (KMB) or fentanyl (25 μg) and 0.5% hyperbaric bupivacaine (8 mg) in group fentanyl-bupivacaine (FB). Heart rate (HR), mean arterial blood pressure (MAP), oxygen saturation, sensorimotor block characteristics, pain-free period, side-effects including: hypotension, bradycardia, nausea, vomiting, sedation, pruritus, respiratory depression and dissociative manifestations, Apgar score at 1 and 5 min, and patients' satisfaction visual analog scores (VAS) were recorded. Patients in group KMB were followed for 6 months in order to assess any neurological disorder. Results: Group KMB showed higher sensory level (P = 0.006), rapid sensory (P = 0.001) and motor (P = 0.005) onsets, prolonged sensory (P = 0.008) and motor (P = 0.002) blocks, and prolonged pain free period (P = 0.002). Ketamine-midazolam stabilized HR and MAP, and significantly reduced incidence of hypotension (P = 0.002), bradycardia (P = 0.013) and vomiting (P = 0.019). Apgar scores at 1 and 5 min were comparable in both groups (P = 0.699 and 0.646 respectively). Patients' satisfaction VAS scores were significantly higher in group KMB (P = 0.001). No patients in KMB group showed dissociative or neurotoxic manifestations. Conclusion: Intrathecal low-dose ketamine combined with midazolam and low-dose bupivacaine stabilizes hemodynamics and prolongs postoperative analgesia without significant side-effects in parturients undergoing CS.